RETRACTED: Prospects of using working water reservoirs in the irrigation mode in the development of the hydro energy industry - Arifjanov Aybek; Xoshimov Sardor; Babajanov Farrukh; Matkaziyev Dilshod; Komilov Sheroz (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001